The Translation Strategies of News Articles on Universitas Gadjah Mada Official Website - Dea Levana; Amin Basuki (Lexicon, 2021)
This research examines the translation strategies applied in the translation of Indonesian articles published on the official website of Universitas Gadjah Mada English into English. The data were collected from 15 articles published in Bahasa Indonesia on the website and their English translations. The analysis and categorization were based on the news translation theory proposed by Bielsa and Bassnett (2009). The results show that all the news translation strategies were applied in the translation of the Indonesian news articles into English. Out of 227 data found in the research, 69 (30.40%) were translated using the elimination strategy, 57 (25.11%) the addition strategy, 24 (10.57%) the summarizing information strategy, 37 (16.30%) the change in the order of paragraphs strategy, and 40 (17.62%) the change of title and lead strategy.